Single-step fabrication of di-titanium nitride thin-film flexible and biocompatible supercapacitor. Issue 23 (1st December 2022) - Sharma, Siddharth; Adalati, Ravikant; Sharma, Meenakshi; Jindal, Shlok; Kumar, Ankit; Malik, Gaurav; Chandra, Ramesh
Abstract: Functional biomedical electronic devices rely on the energy storage units such as batteries and capacitors as their sole power sources. These power sources are constrained by issues such as low performance, non-biocompatibility, and lack of flexibility. In this work, nanocluster di-titanium nitride (n-Ti2 N) thin films were sputtered onto the surface of 304 stainless steel substrate (SS-304) for the fabrication of a highly efficient symmetric supercapacitor device. The electrochemical studies were performed in Phosphate Buffer Saline (PBS) at different current densities and scan rates. The n-Ti2 N@SS electrode-based symmetric supercapacitor device shows high areal energy density of 1.614 μWhcm −2 with optimum areal power-density of 49.98 mWcm −2 . The device evinces a broader voltage window of 1.0 V with good capacitance retention of 86% even after 5000 CV cycles at a scan rate of 50 mVs −1 . The biocompatibility of the electrode was checked in-vitro and it reveals excellent cell viability of around 85%. The SS device also performs ideally in bending state. Owing to these appealing properties, the proposed SS device can be considered potentially suitable for powering the battery-operated implantable biomedical devices (such as pacemakers, Implantable Cardiovert Defibrillators ICD, Cardiac Resynchronization Therapy CRT, and cochlear implants) and wearable electronics. Graphical abstract: Image 1